2013
DOI: 10.1038/ejhg.2013.214
|View full text |Cite
|
Sign up to set email alerts
|

Two ABCB4 point mutations of strategic NBD-motifs do not prevent protein targeting to the plasma membrane but promote MDR3 dysfunction

Abstract: The ABCB4 gene encodes for MDR3, a protein that translocates phosphatidylcholine from the inner to the outer leaflet of the hepatocanalicular membrane; its deficiency favors the formation of 'toxic bile'. Several forms of hepatobiliary diseases have been associated with ABCB4 mutations, but the detrimental effects of most mutations on the encoded protein needs to be clarified. Among subjects with cholangiopathies who were screened for mutations in ABCB4 by direct sequencing, we identified the new mutation p.(L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…A similar conclusion was drawn for another missense mutation associated with intrahepatic cholestasis of pregnancy . Recently, a study demonstrated that two mutations found in patients with biliary diseases, Y403H and L481R, decreased ABCB4 activity without altering its membrane targeting . These mutations were localized in the first nucleotide‐binding domain and therefore may affect ABCB4 function by interfering with ATP binding and/or hydrolysis.…”
Section: Discussionsupporting
confidence: 58%
“…A similar conclusion was drawn for another missense mutation associated with intrahepatic cholestasis of pregnancy . Recently, a study demonstrated that two mutations found in patients with biliary diseases, Y403H and L481R, decreased ABCB4 activity without altering its membrane targeting . These mutations were localized in the first nucleotide‐binding domain and therefore may affect ABCB4 function by interfering with ATP binding and/or hydrolysis.…”
Section: Discussionsupporting
confidence: 58%
“…We have shown that the I541F mutation identified in a PFIC3 patient caused misfolding and retention of the protein in the endoplasmic reticulum . Subsequent studies have reported some mutations that reduced PC secretion or affected ABCB4 protein expression . The aim of these studies was primarily to correlate ABCB4 mutations with patients' phenotypes.…”
mentioning
confidence: 99%
“…(14,15) Subsequent studies have reported some mutations that reduced PC secretion or affected ABCB4 protein expression. (12,(16)(17)(18) The aim of these studies was primarily to correlate ABCB4 mutations with patients' phenotypes.…”
mentioning
confidence: 99%
“…The lipids accumulated in the culture medium (presumably bound to an acceptor in the added calf serum) and were quantified by thin layer chromatography. Whereas stable cells have been used to characterize suspected disease-associated ABCB4 mutants, this is probably impractical for the large number of idiopathic non-synonymous single nucleotide polymorphisms (SNPs) that have been reported [50]. To develop a high(er) throughput analytical system to relate genotype and phenotype at the protein level required an understanding of the link between PC flopping and PS flipping.…”
Section: The Importance Of Cellular Models To Study Lipid and Bile Samentioning
confidence: 99%